lncRNA FER1L4 is dysregulated in osteoarthritis and regulates IL-6 expression in human chondrocyte cells - Jinhai He (Nature Portfolio, 2021)
Abstract Osteoarthritis (OA) is the most prevalent joint disease and is one of the major causes of disability in the world. There has been an increase in the incidence of OA, which is associated with an aging population, sedentary lifestyle, and reduced physical activity. Due to the complex OA pathogenesis, there are limited diagnostic tools. OA is a degenerative joint disorder with a recognized inflammatory component, usually described as abnormal expression of inflammatory factors. For instance, interleukin 6 (IL‐6) has been shown to be upregulated in serum and synovial fluid among patients with OA. Most of the inflammatory factors have been associated with the expression of long noncoding RNAs (lncRNAs). However, the role of the novel lncRNA Fer-1-like protein 4 (FER1L4) in OA is yet to be determined. Here, we interrogated the expression profile of FER1L4 in patients with OA to define its potential application as a diagnostic marker. We collected synovial fluid and blood samples from both OA cases and normal controls. Using qRT-PCR, we evaluated the expression of FER1L4 in plasma and synovial fluid. On the other hand, the expression of IL-6 in plasma and synovial fluid was assessed using ELISA. Besides, the effect of age, gender or disease stage in the expression of the FER1L4 in plasma was also estimated. Moreover, the receiver operating characteristic (ROC) curves were used to determine the impact of FER1L4 in OA cases compared with the normal controls. In addition, we analyzed the correlation between FER1L4 and IL-6 through Pearson correlation analysis. Also, IL-6 expression in overexpressed FER1L4 samples was detected in chondrocytes through western blot analysis, while FER1L4 expression following endogenous IL-6 exposure was detected by qRT-PCR. Our data showed that whereas lncRNA FER1L4 is downregulated in OA patients, IL‐6 is upregulated. The plasma FER1L4 levels among the OA cases were suppressed with disease progression and old age, and the down-regulation could efficiently discriminate OA patients from normal subjects. In addition, upregulation of FER1L4 inhibited IL‐6 expression in human chondrocyte cells, and treatment with different concentrations of exogenous IL‐6 did not affect the expression of FER1L4. Taken together, our data demonstrates that FER1L4 could efficiently identify OA cases from normal subjects, and can also modulate the expression of IL‐6 in human chondrocytes.